The Difference of Prevalence of Using Iodium Salt In Household And Growth of Stature of Students In Beringkit Belayu Village And Batannyuh Village Marga District Tabanan Regency - I Gusti Agung Ningrah Jayam Utami; I Made Purnadhibrata; Ni Made Yuni Gumala (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
The use of iodized salt is very important to prevent disruption due to lack ofiodized salt and affect the growth height of students. Beringkit Belayu Village has organized a socialization of the use of iodized salt through distribution at the posyandu every month, while other villages have not yet socialized the use of iodized salt. The aims of this study was to determine the differences of prevalence of using iodium salt in household and growth height of students in Beringkit Belayu Village and Batannyuh village Marga district Tabanan regency. This research is a observasional study with a cross sectional approach and we got the sample total are 65 samples. We used chi square and t-test to analyzed data. Based on the results of the analysis, it is known that: there is a difference in the prevalence of iodized salt use in households in Beringkit Belayu and Batannyuh villages (p = 0.006) and there are no differences in height growth for studets in Beringkit Belayu village and Batannyuh village (p=0.83). Keywords: house hold, students, iodized salt, growth of stature